The efficacy and accuracy of 3D-guided orthodontic piezocision: a randomized controlled trial - Omar Gibreal; Yasser Al-modallal; Ghiath Mahmoud; Ahmad Gibreal (BMC, 2023)
Abstract Background No randomized controlled trial (RCT) has studied the accuracy of surgical guides used in terms of orthodontic treatment acceleration. Therefore the aim of this trial was to assess computer-guided piezocision-based orthodontic. Materials and methods Thirty-two patients with severely crowded upper anterior teeth were enrolled and randomly allocated to either the experimental group (ExpG) or the control one. Subjects of the ExpG received three-dimensional (3D) guided piezoelectric corticotomies on the buccal alveolar bone of the anterior region. Five piezocision cuts were properly performed between each anterior teeth and the adjacent in virtual models. Surgical guides were designed and 3D-printed with preplanned slots that guide gingival and then piezoelectric incisions. The patients underwent Cone-Beam Computed Tomography CBCT before and immediately after surgery. Thus, Predesigned piezocisions were compared to the actual ones in attempt to measure three dimensional deviations of the applied peizocisions. Results Ninety-six severe maxillary dental crowding were assigned for eligibility, 40 of them met the inclusion criteria. Thirty-two participants were randomly allocated to the trial`s groups. No patient was lost to follow-up neither from the control nor the experimental group. Overall alignment time (OAT) was reduced by 53% in the experimental group compared to the control group. The mean of the 3D deviation of the surgical guide was 0.23 mm (standard deviation 0.19 mm). Conclusion The values of the surgical guide deviation was nearly null, which confirms that this innovative technique is clinically applicable. Furthermore, this technique was impressively effective in accelerating orthodontic tooth movement. Trial registration This trial was registered at The ISRCTN registry (ID: ISRCTN65498676 Registration date: 07/04/2021).